The Failure of Cotton Imperialism in Africa: Did Agricultural Seasonality undermine Colonial Exports? - Michiel de Haas (African Economic History Network (AEHN), 2020)
European colonizers sought to extract cotton from sub-Saharan Africa. However, while some African farmers generated substantial cotton output, most others did not. I revisit a thesis proposed by John Tosh (1980), to argue that patterns of agricultural seasonality played a crucial role in these heterogeneous outcomes. A comparison of widespread cotton adoption in British Uganda and persistent cotton failure in the French West African interior highlights the impact of rainfall seasonality on farmers' production possibilities and subsistence risks. Ugandan output was enabled by long rainy seasons, smoothing labor requirements and allowing farmers to assess the food harvest before committing to cotton planting. These combined effects resulted in an estimated 4 to 5 times larger capacity to grow cotton alongside food crops. A belated take-off in post-colonial Francophone West Africa illustrates how the observed historical seasonality constraint was contingent on technological stagnation and thin food markets, which characterized most parts of colonial Africa.
Keywords: N17; N37; N57; 330; Africa; Cotton; Imperialism; Seasonality